Diagnostic Model for Supporting the Development of Health-conscious Organizational Behavior - Karoliny, Mártonné (International Journal of Engineering and Management Sciences, 2016)
In the 21st century more and more countries of the world take the attitude that human health is not just an issue for healthcare services but for all major areas of life. Such an area for employees is the workplace. Protection of employee health and safety has for a long time been a non-transferable (objective) obligation and responsibility for employers in Europe. Connections between health and the workplace have however extended far beyond the traditional aspect of safety and health at work. Developing a health-conscious organisational behaviour means a challenge for many Hungarian companies; the model described in this study assists them in both diagnosing their current situation and choosing the appropriate course, method and tools for development.